Unification of Ukrainian Society in a Postwar Period as a Preventive Mechanism to Avert the Crisis of State - Lavrynenko, Hanna; Donaj, Łukasz (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa UAM, 2023)
The study involves the analysis of unification of Ukrainian society in a postwar period to prevent the crisis of state system. It is claimed, that upon the war termination the issue of creation of universal Ukrainian society forming model arises, which is supposed to represent a symbiosis of foundations of nationwide well-being and prospects of Ukraine strategic development. It is shown, that the existent division of society into those who stayed in Ukraine and those who left for other countries can scale up in a long run. The loss of conceptual univocity in the course of developing such categories as “victim,” “patriot,” “traitor” and “savior” in civil society bears evidence to the mobility of self-identification process of existing population clusters and possible appearance of new categories of populace in the not so distant future. The rationalization for human capital is provided as well as the necessity of having regard to the mentioned factor while elaborating the postwar country development strategy. Special attention is paid to the problem of implementation of repatriation policy. Its types are defined, and the mostly acceptable options for Ukraine are characterized, including the direct and active or in direct and mediated state’s stimulation of nationals’ returning to the ethnical Homeland. Based on the conducted analysis of current experience of European countries, it was concluded that it is the controlled process of return migration that is the key component of consistent country development. Przedmiotem publikacji jest analiza procesu unifikacji społeczeństwa ukraińskiego – w okresie powojennym – jaki jest niezbędny by zapobiec kryzysowi państwa. Zdaniem autorów, po zakończeniu wojny palącym problemem będzie kwestia stworzenia uniwersalnego modelu kształtowania się społeczeństwa ukraińskiego, którego zadaniem będzie symbioza podstaw ogólnonarodowego dobrobytu oraz perspektyw strategicznego rozwoju Ukrainy. Podkreślono, że istniejący podział społeczeństwa na tych, którzy pozostali na Ukrainie i tych, którzy wyjechali do innych państw, w dłuższej perspektywie może się pogłębiać. Utrata jednoznaczności pojęciowej – w toku kształtowania się społeczeństwa obywatelskiego – takich kategorii jak „ofiara”, „patriota”, „zdrajca” i „zbawiciel” świadczy o mobilności procesu samoidentyfikacji istniejących skupisk ludności i możliwym – w niedalekiej przyszłości – pojawieniu się nowych kategorii ludności. Przedstawiono również zagadnienie racjonalnego wykorzystania kapitału ludzkiego oraz konieczność uwzględnienia tego czynnika przy opracowywaniu powojennej strategii rozwoju państwa. Szczególną uwagę zwrócono na problem realizacji polityki repatriacyjnej. Zdefiniowano jej rodzaje i scharakteryzowano najbardziej akceptowalne opcje dla Ukrainy, w tym bezpośrednie i aktywne lub pośrednie i stymulowane przez państwo powroty obywateli do etnicznej Ojczyzny. Na podstawie przeprowadzonej analizy dotychczasowych doświadczeń państw europejskich uznano, że to właśnie kontrolowany proces migracji powrotnych jest kluczowym elementem spójnego rozwoju państwa.
Unifikacja społeczeństwa ukraińskiego w okresie powojennym jako mechanizm zapobiegania kryzysowi państwa
Keywords: civil society; return migration; repatriation policy; state; unification of society; universalization; safety; crisis of state system; społeczeństwo obywatelskie; migracje powrotne; polityka repatriacyjna; państwo; unifikacja społeczeństwa; uniwersalizacja; bezpieczeństwo; kryzys państwa